2015
DOI: 10.1245/s10434-015-4418-2
|View full text |Cite
|
Sign up to set email alerts
|

The miR-506-Induced Epithelial–Mesenchymal Transition is Involved in Poor Prognosis for Patients with Gastric Cancer

Abstract: The EMT was directly suppressed by miR-506, and its low expression was an independent prognostic factor in gastric cancer patients. The data indicated that miR-506 may act as a tumor suppressor and could be a novel therapeutic agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…miR-506, located on chromosome x, has been reported to be involved in diverse biological behaviors depending on different target genes. It has been shown that miR-506 expression is downregulated in several types of cancers such as gastric (18), cervical (14), ovarian (21) and lung cancer (22), suggesting that miR-506 plays an important role in tumorigenesis and tumor progression. Yang et al reported that miR-506 is downregulated in clear cell renal cell carcinoma and inhibits cell growth and metastasis via targeting forkhead box Q1 (FLOT1) (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…miR-506, located on chromosome x, has been reported to be involved in diverse biological behaviors depending on different target genes. It has been shown that miR-506 expression is downregulated in several types of cancers such as gastric (18), cervical (14), ovarian (21) and lung cancer (22), suggesting that miR-506 plays an important role in tumorigenesis and tumor progression. Yang et al reported that miR-506 is downregulated in clear cell renal cell carcinoma and inhibits cell growth and metastasis via targeting forkhead box Q1 (FLOT1) (23).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small (19-24 nucleotides), single-stranded, non-coding RNA molecules (18)(19)(20)(21)(22)(23)(24) that usually lead to gene silencing by binding to complementary sequences in the three prime untranslated regions (3'UTRs) of target messenger RNA (mRNA) transcripts (6)(7)(8). miRNAs are involved in various biological processes, such as cell division, cell cycle, differentiation, proliferation development and apoptosis (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, miR-506 suppressed the metastasis of breast cancer cells by targeting the IQ motif containing GTPase-activating protein 1 (29). In gastric cancer, miR-506 inhibited EMT by targeting ETS1 (37) or SNAI2 (38). miR-506 also suppressed the proliferation and invasion of gastric cancer cells by targeting Yap1 (39).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-506 was identified as a member of the miR-506-514 cluster, which includes seven distinct miRNAs: miR-506, -507, -508, -509, -510, -513 and miR-514 [14,15]. Besides, its abnormal expression was detected to be associated with multiple benign diseases and malignant carcinomas [16][17][18][19][20]. Wen et al reported that miR-506 exerted its anti-proliferative function by directly targeting Gli3 in human CC [21].…”
mentioning
confidence: 99%